Tersilochinae (Hymenoptera: Ichneumonidae) of Costa Rica, part 1. Genera Allophrys Förster, Barycnemis Förster and Meggoleus Townes - Khalaim, Andrey I.; Broad, Gavin R. (Zootaxa, 2012)
The Costa Rican fauna of three tersilochine genera, Allophrys Förster, Barycnemis Förster and Meggoleus Townes, is re-vised. Seven species, A. barycnemica sp. nov., A. bribria sp. nov., A. compressor sp. nov., A. hansoni sp. nov., A. mega-frons sp. nov., A. noyesi sp. nov. and B. costaricensis sp. nov., are described as new. Allophrys divaricata Horstmann, M.spirator Townes and two groups of undescribed species of Allophrys are newly recorded from Costa Rica. A key to theCosta Rican species of Allophrys is provided. Finger-shaped sensory flagellar structures, previously known in two European species of Phradis Förster, are registered in all Costa Rican species of Allophrys, Barycnemis and Meggoleus.